Multiple Recipients of the Večernica Award and Their Canonization in the Slovenian Educational System: An Analysis through Theories of Cultural Memory - Mileva Blažić, Milena (Trideset let literarne nagrade večernica, 2026)
This study examines the canonisation of four multiple winners of the Večernica award, Slovenia's most prestigious prize for children's and young adult literature, through the lens of cultural memory theory. Using Dović's (2012) three-phase canonisation model and Juvan's (2005) framework of literature as a medium of cultural memory, the research analyses the institutional presence of Peter Svetina (three-time Večernica winner), Janja Vidmar (two-time winner), Marjana Moškrič (two-time winner), and Andrej E. Skubic (two-time winner) in Slovenia's educational system. Data sources include the 2025 National Curriculum, the Cankarjevo competition (1997–2026), the 2025 Anthology, and international nominations (IBBY, ALMA). Results demonstrate complete institutional canonisation through confirmation (state curriculum), indoctrination (mandatory reading and competitions), and procreativity (secondary corpus formation). Peter Svetina achieves international hypercanonisation as Slovenia's only two-time Hans Christian Andersen Award finalist. The study confirms Juvan's (2005) thesis that the literary canon is the primary vehicle for transmitting cultural memory through educational institutions.